Dynamic behavior analysis of a rigid rotor supported by hydrostatic squeeze film dampers compensated with new electrorheological valve restrictors. Issue 5 (4th November 2019) - Benadda, Mohamed; Bouzidane, Ahmed; Thomas, Marc; Guilbault, Raynald
Abstract : Purpose: This paper aims to propose a new hydrostatic squeeze film damper compensated with electrorheological valve restrictors to control the nonlinear dynamic behavior of a rigid rotor caused by high unbalance eccentricity ratio. To investigate the effect of electrorheological valve restrictors on the dynamic behavior of a rigid rotor, a nonlinear model is developed and presented. Design/methodology/approach: The nonlinear results are compared with those obtained from a linear approach. The results show good agreement between the linear and nonlinear methods when the unbalanced force is small. The effects of unbalance eccentricity ratio and electric field on the vibration response and the bearing transmitted force are investigated using the nonlinear models. Findings: The results of simulation performed that the harmonics generated by high unbalance eccentricities can be reduced by using hydrostatic squeeze film damper compensated with electrorheological valve restrictors. Originality/value: The numerical results demonstrate that this type of smart hydrostatic squeeze film damper provides to hydrostatic designers a new bearing configuration suitable to control rotor vibrations and bearing transmitted forces, especially for high speed.